An Analysis Magical Realism of Supernatural Phenomena As Seen in Lewiis Carroll’s Alice in Adventures Wonderland - Helmita, Helmita; Salsabila, Melinia (Jurnal Ilmiah Langue and Parole, 2024)
The title of this research is "An Analysis of Magical Realism of Supernatural phenomena As Seen in Lewis Carroll's Alice's Adventures in Wonderland". The problem of this research is focused on the characteristics of magical realism, inanimate objects that come alive as reflected in the novel Alice's Adventures in Wonderland. This research is a qualitative descriptive research. The technique used in this research is literature. To obtain certain data by searching and collecting several books related to the analysis of magical realism, the characteristics of magical realism, inanimate objects that come alive in a literary work. By quoting sentences or words that show the characteristics of magical realism, the dead band that turns into life then describes it. Magical reality includes four parts, namely the irreducible element, the characteristic phenomenal world, the amalgamation of nature, the disturbance of time and space. This happens due to Alice's life in her dream world which gets lost in the rabbit hole and indeed this novel tells magic so that everything that Alice experiences is beyond reason. The change in the reality of inanimate objects to life occurs due to the characters reflected in the novel which should not have happened in real life. Like a talking rabbit, a rabbit's glove that can take off and walk on its own. Even other animals that can talk. Lessons can be learned from this novel, such as the struggle for life, in life, don't give up even though the obstacles you face are great. Always be a good person, always support the truth.